Pliocene flora from S. Pedro da Torre deposits (Minho, NW Portugal) - Vieira, Manuel Carlos Marques (2011)
This paper deals with the systematic and botanical description of the microfloral elements from the Pliocene S. Pedro da Torre section (NW Portugal) and the description of the palaeoenvironment and palaeoclimate, for use as a correlation attempt with other Pliocene deposits. The S. Pedro da Torre section represents one of the main sites which may help us to understand the vegetation and the paleoenvironment of the Pliocene north-western Iberian Peninsula. Nearly 70 different taxa were indentified (including bryophytes, ferns, gymnosperms and angiosperms), which indicate a palaeowetland setting, dominated by arboreal vegetation that developed under humid and warm climatic conditions.